PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada karyawan PT. Selecta Kota Wisata Batu) - Nuri Nuri; Abdul Kodir Djaelani; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study aims to determine how the influence of work motivation, work environment and work discipline variables on the performance of employees of PT. Selecta Batu Tourism City. Research is used by using explanatory methods with quantitative methods on employees of PT. Selecta Batu Tourism City. The sample used in this study amounted to 57 employees. The analytical method used in this study is using the SPSS program which consists of several instrument tests, normality tests, classic assumption tests, multiple linear regression analysis and hypothesis testing. The results of this study indicate that work motivation variables partially influence employee performance, work environment variables do not affect employee performance and work discipline variables do not affect employee performance. Keywords: Employee Performance, Work Motivation, Work Environment and Work Discipline